Library Staff Need More Support in Order to Alleviate Teaching Anxiety - Koos, Jessica A. (Evidence Based Library and Information Practice, 2021)
A Review of: Lundstrom, K., Fagerheim, B. & Van Geem, S. (2021). Library teaching anxiety: Understanding and supporting a persistent issue in librarianship. College & Research Libraries, 82(3), 389-409. https://doi.org/10.5860/crl.82.3.389 Abstract Objective – To determine academic librarians’ attitudes towards their teaching, how teaching anxiety manifests itself, and how teaching anxiety affects these attitudes. Design – Online Survey. Setting – The survey was distributed through various library science listservs. Subjects – Any library staff with a teaching component in their role were invited to respond. There was a total of 1,035 initial responses. Methods – The survey questions were based on a previously published survey about teaching anxiety by Davis (2007). However, the survey for this study added questions about formal and self-diagnosis of other types of anxieties, physical and psychological anxiety symptoms, and how teaching anxiety impacts other areas of the respondents’ lives. There were also questions on potential supports to reduce teaching anxiety, as well as potential barriers to these supports. Main Results – It was found that approximately 65% of respondents experience teaching anxiety. Approximately 40% of those respondents were formally diagnosed with anxiety, and approximately 42% were self-diagnosed. There was a significant association between a formal diagnosis of anxiety, and teaching anxiety. There were also significant associations between past training, preparation, and teaching anxiety, with anxiety occurring less with increased training and preparation. Conclusion – Teaching anxiety is a significant issue among library staff. Supports in the form of workshops on teaching as well as coping with anxiety can possibly help to reduce this phenomenon.